Co-optation and Repression of Religion in Authoritarian Regimes - Schleutker, Elina (Politics and religion, 2021)
Comparative research on authoritarianism has largely neglected religion. Yet, in order to understand the logic of authoritarian control over the civil society, it is necessary to study how the authoritarian regimes deal with religious groups. In this paper, lessons from the two rapidly expanding fields on regulation of religion and comparative authoritarianism are combined. In particular, a conceptualization of regulation of religion in the authoritarian context is proposed, according to which positive endorsement of religion can be understood as co-optation, whereas negative restrictions can be seen as repression. By employing data on positive endorsement and negative restrictions on religion from 2014 for ca. 70 countries, three different clusters of authoritarian countries regarding the regulation of religion are identified. Finally, it is argued that capacity and ambition of both the religious groups and the authoritarian regimes are the main determinants of regulation.